2008
DOI: 10.1007/s12028-007-9043-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Balance and Blood Volume Measurement after Aneurysmal Subarachnoid Hemorrhage

Abstract: Calculations of fluid balance do not provide adequate information on actual CBV after SAH, as measured by PDD. This raises doubt whether fluid management guided by fluid balances is effective in maintaining normovolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 32 publications
(35 reference statements)
1
45
1
Order By: Relevance
“…This is in contrast with the hypothesis that BNP would lead to urinary sodium and water excretion as seen in CSW. Previous studies have shown that fluid balances are not correlated to actual circulating blood volume, what can explain why the authors found high BNP concentrations associated with severe hypovolemia measured with PDD, but not with more urine production or lower fluid balances [12]. Several reports found CSW to be the most common cause of hyponatremia after intracranial disease, including SAH [3,7,13,[26][27][28].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is in contrast with the hypothesis that BNP would lead to urinary sodium and water excretion as seen in CSW. Previous studies have shown that fluid balances are not correlated to actual circulating blood volume, what can explain why the authors found high BNP concentrations associated with severe hypovolemia measured with PDD, but not with more urine production or lower fluid balances [12]. Several reports found CSW to be the most common cause of hyponatremia after intracranial disease, including SAH [3,7,13,[26][27][28].…”
Section: Discussionmentioning
confidence: 93%
“…In CSW, patients are hyponatremic due to active urinary sodium excretion and not to water retention and patient are therefore hypovolemic. The key feature to differentiate between the two syndromes is volume status, but circulatory volume status is very difficult to assess on clinical or biochemical grounds [11,12]. Outside the context of SAH, SIADH is treated by fluid restriction and CSW by sodium and fluid replacement.…”
Section: Introductionmentioning
confidence: 99%
“…2,6,7 BV values were classified as normal (60 to 80 mL/kg), moderate hypovolemic (50 to 60 mL/kg), severe hypovolemic (Ͻ50 mL/kg), or hypervolemic (Ͼ80 mL/kg). 6,8 The goal of fluid management was to maintain normovolemia. At admission, an infusion of 3 L normal saline per day was installed, in addition to oral intake as desired by the patient.…”
Section: Methodsmentioning
confidence: 99%
“…Fluid balance does not necessarily reflect intravascular volume [29]. Some have advocated CVP while others rely on PAC to optimize volume status.…”
Section: Volume Statusmentioning
confidence: 99%